Perancangan Aplikasi Sistem Informasi Akuntansi Laporan Keuangan Dengan Menggunakan Microsoft Access 2016 (Studi Kasus Pada PT Maju Industri Indonesia) - Nadira Fadhila Huda; Etti Ernita Sembiring (Labkat Press KA FTIK UNIKOM, 2022)
This research aims to design a program or application of a computerized financial statement accounting information system using Microsoft Access to overcome the obstacles faced by PT. Maju Industri Indonesia. PT Maju Industri Indonesia still records financial transactions and prepares financial reports semi manually and there are still some obstacles in its use. The recording of financial transactions and the preparation of financial statements at PT Maju Industri Indonesia still uses Microsoft Excel and the recording is done on several separate documents so that the preparation of financial statements is still inputted manually. This causes the procedures for preparing financial statements to be less effective and efficient and can hamper the company’s operational activities. Therefore, it is necessary to apply a computerized and technology based financial statement accounting information system to improve the efficiency and effectiveness of the preparation and presentation of financial statements. This research is a qualitative research with a descriptive analytical and developmental case study approach. Data collection methods used are observation and interviews with the company. The results of this study are in the form of designing financial report application programs using Microsoft Access 2016 and other tools in the form of data flow charts and document flowcharts. The results of the design of this financial statement accounting information system application program are expected to solve the problems and constraints that occur at PT Maju Industri Indonesia.